Effect of Piper Betle extract hand sanitizer in reducing microbes on hands by using Fingertips Touch Plate Method - Ahmad Nordin, Norain; Muhammad, Khairunnisa; Mohamed Noor, Mashitah; Manizira K. Leny Annan (Multidisciplinary Applied Research and Innovation, 2021)
This study was performed to evaluate the effectiveness of Piper betle hand sanitizer by using 70% ethanol and 0.2% benzalkonium chloride (BKC) as compulsory ingredients in reducing Staphylococcus aureus on hands, as compared with the 70% ethanol-based hand sanitizer (ESH) and 0.2% benzalkonium chloride-based hand sanitizer (BKCHS) alone. Fingertips touch plate method were obtained from three students in which all three students used five different types of hand sanitizers which are Piper betle hand sanitizer, Piper betle with 70% ethanol hand sanitizer (ESH), Piper betle with 0.2% benzalkonium chloride hand sanitizer (BKCSH), ESH and BKCHS. The pH value of all hand sanitizers was taking before test. The observation of bacterial colonies was obtained after three days. The total number, mean and percentage of bacterial colonies were calculated to compare the differences of them between five different types of hand sanitizers. The results showed a significant reduction in total bacterial colony counts of Staphylococcus aureus after three days of using different types of hand sanitizers. There was a significant decrease in Staphylococcus aureus on the fingertips of students in the Piper betle with 70% EHS and Piper betle with 0.2% BKCHS as compared to the Piper betle hand sanitizer, ESH and BKCHS.